Digital frequency synthesis demystified : DDS and fractional-N PLLs - Goldberg, Bar-Giora (LLH Technology, 1999)
In-depth coverage of modern digital implementations of frequency synthesis architectures Numerous design examples drawn from actual engineering projects The accompanying CD includes digital frequency synthesis design tools and an electronic version of the book Digital frequency synthesis is used in modern wireless and communications technologies such as radar, cellular telephony, satellite communications, electronic imaging, and spectroscopy. This is book is a comprehensive overview of digital frequency synthesis theory and applications, with a particular emphasis on the latest approaches using fractional-N phase-locked loop technology. The design tools in the accompany CD allow readers to work through the examples in this book for a realistic simulation of actual design using digital frequency synthesis. In-depth coverage of modern digital implementations of frequency synthesis architectures Numerous design examples drawn from actual engineering projects The accompanying CD includes digital frequency synthesis design tools and an electronic version of the book.